ROMANTISME ISLAM DAN POLITIK DALAM HIZBUT TAHRIR: STUDI PEMIKIRAN TAQĪ AL-DĪN AL-NABHĀNĪ - Mohamad Khusnial Muhtar (LP2M Universitas Ibrahimy, 2024)
Hizbut Tahrir, an organization banned in various countries, including Indonesia, is believed to remain covertly active at the grassroots level. This research aims to reveal the underlying philosophy fueling this persistent movement specifically, the romantic interplay between Islam and politics. Examining this relationship through the perspective of its founder, Taqī al-Dīn al-Nabhānī, the study explores both ideological and practical implications. Utilizing the Systematic Literature Review (SLR) method with a philosophical approach and qualitative analysis and referencing al-Nabhānī’s works, particularly Nidham ul-Islam (The System of Islam), findings indicate that Hizbut Tahrir is motivated by a mission to establish a comprehensive application of Sharia through the Khilafah Islamiyyah as the political realization of Islamic ideals. Islam and politics are seen as interconnected, with Islam as a complete divine guide and politics as essential for effective Sharia implementation. Theoretically, further research is needed on the resilience of ex-members and current societal perceptions amidst evolving ideologies with current field data. Practically, a re-evaluation of Islamic understanding in a modern context is necessary to ensure that Islamic values are applied adaptively and relevantly to contemporary challenges.